Isatuximab, carfilzomib, and dexamethasone in relapsed multiple myeloma (IKEMA): a multicentre, open-label, randomised phase 3 trial. Issue 10292 (19th June 2021) - Moreau, Philippe; Dimopoulos, Meletios-Athanasios; Mikhael, Joseph; Yong, Kwee; Capra, Marcelo; Facon, Thierry; Hajek, Roman; Špička, Ivan; Baker, Ross; Kim, Kihyun; Martinez, Gracia; Min, Chang-Ki; et al.
Summary: Background: Isatuximab is an anti-CD38 monoclonal antibody approved in combination with pomalidomide–dexamethasone and carfilzomib–dexamethasone for relapsed or refractory multiple myeloma. This phase 3, open-label study compared the efficacy of isatuximab plus carfilzomib–dexamethasone versus carfilzomib–dexamethasone in patients with relapsed multiple myeloma. Methods: This was a prospective, randomised, open-label, parallel-group, phase 3 study done at 69 study centres in 16 countries across North America, South America, Europe, and the Asia-Pacific region. Patients with relapsed or refractory multiple myeloma aged at least 18 years who had received one to three previous lines of therapy and had measurable serum or urine M-protein were eligible. Patients were randomly assigned (3:2) to isatuximab plus carfilzomib–dexamethasone (isatuximab group) or carfilzomib–dexamethasone (control group). Patients in the isatuximab group received isatuximab 10 mg/kg intravenously weekly for the first 4 weeks, then every 2 weeks. Both groups received the approved schedule of intravenous carfilzomib and oral or intravenous dexamethasone. Treatment continued until progression or unacceptable toxicity. The primary endpoint was progression-free survival and was assessed in the intention-to-treat population according to assigned treatment. Safety was assessed in all patients who received at least one dose according to treatment received. The study is registered at ClinicalTrials.gov, NCT03275285 . Findings: Between Nov 15, 2017, and March 21, 2019, 302 patients with a median of two previous lines of therapy were enrolled. 179 were randomly assigned to the isatuximab group and 123 to the control group. Median progression-free survival was not reached in the isatuximab group compared with 19·15 months (95% CI 15·77–not reached) in the control group, with a hazard ratio of 0·53 (99% CI 0·32–0·89; one-sided p=0·0007). Treatment-emergent adverse events (TEAEs) of grade 3 or worse occurred in 136 (77%) of 177 patients in the isatuximab group versus 82 (67%) of 122 in the control group, serious TEAEs occurred in 105 (59%) versus 70 (57%) patients, and TEAEs led to discontinuation in 15 (8%) versus 17 (14%) patients. Fatal TEAEs during study treatment occurred in six (3%) versus four (3%) patients. Interpretation: The addition of isatuximab to carfilzomib–dexamethasone significantly improves progression-free survival and depth of response in patients with relapsed multiple myeloma, representing a new standard of care for this patient population. Funding: Sanofi. Video Abstract: Video abstract YouTube link: https://youtu.be/5kXtQQlzRh4